2018
DOI: 10.1002/ece3.3849
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional geometry and fitness consequences in Drosophila suzukii, the Spotted‐Wing Drosophila

Abstract: Since its arrival to North America less than a decade ago, the invasive Spotted‐Wing Drosophila (Drosophila suzukii) has inflicted substantial economic losses on soft fruit agriculture due to its ability to oviposit into ripening fruits. More effective management approaches for this species are needed, but little is known about the factors that influence behavioral choices made by D. suzukii when selecting hosts, or the consequences that their offspring experience when developing in different environments. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 56 publications
5
66
0
4
Order By: Relevance
“…One study showed that larval survival was highest on P:C 1:2 diets, while survival was decreased at lower protein diets (1:16, no carbohydrateonly diet was tested; Silva-Soares et al, 2017). Similarly, another study showed that more D. suzukii larvae survive on protein-rich diets (P:C 24:1), while survival was decreased at lower protein diets (P:C 1:12; Young, Buckiewicz, & Long, 2018). Comparing with these studies, our study suggests that different developmental stages may have different dietary requirements in D. suzukii.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that larval survival was highest on P:C 1:2 diets, while survival was decreased at lower protein diets (1:16, no carbohydrateonly diet was tested; Silva-Soares et al, 2017). Similarly, another study showed that more D. suzukii larvae survive on protein-rich diets (P:C 24:1), while survival was decreased at lower protein diets (P:C 1:12; Young, Buckiewicz, & Long, 2018). Comparing with these studies, our study suggests that different developmental stages may have different dietary requirements in D. suzukii.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, "Acolon" attracted more females than "Müller-Thurgau", but final oviposition was rather low in the first, and almost zero in the latter variety. Thus, while for the first attraction color, most likely together with volatiles [25], may be important cues for attraction, additional physical, and chemical cues determine the final host acceptance for oviposition [30], which should be investigated in more detail in future studies. In this regard, fruit firmness or skin penetration force are discussed to play a relevant role in D. suzukii oviposition ability, finding decreasing infestation with increasing penetration force [15,21,45].…”
Section: Discussionmentioning
confidence: 99%
“…Various visual, physical, and chemical factors may affect D. suzukii preference behavior for different plant species and varieties and offspring performance in different fruits, such as volatiles, size, color, skin firmness and penetration force, maturity, sugar content, acidity, and nutrient content [16,17,[25][26][27][28][29][30]. For example, D. suzukii utilizes visual cues such as fruit color as remote sensory information for host location [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in slower establishment and build‐up of laboratory population and more time and care to rear them (Iacovone et al., ; personal observations). However, with increasing knowledge on the fly's biology (e.g., Hamby et al., ) and culturing methods (e.g., Sampson et al., ; Young, Buckiewicz, & Long,), (mass) rearing is becoming more feasible. Once a large population has been established, it can be kept under the right laboratory conditions.…”
Section: Step 4: Improve and Determine The Success Of The Parasitoidmentioning
confidence: 99%